YAYLOV YERLARIDAN FOYDALANISH BO‘YICHA XORIJIY TAJRIBALAR - Erkinova M.L (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article analyzes the experience of leading countries in the use, management and evaluation of pasture lands. In particular, it discusses land use practices, taxation systems, leasing policies, and modern monitoring technologies in countries such as the USA, China, Kazakhstan, Russia, Canada, and Australia. The article also addresses the application of NDVI and other vegetation indices in pasture monitoring.